STUDI INTERAKSI DAN PREDIKSI TOKSISITAS AKUATIK SENYAWA DALAM BAWANG TIWAI (Eleutherine americana (Aubl.) Merr. ex K.Heyne) SEBAGAI KANDIDAT ANTIFUNGI DAN ANTITOKSOPLASMOSIS SECARA IN SILICO - Athifah Salim Martak, Nadiyah
Antifungal drugs development is relatively slower than antibacterial drugs because of the similarity in fungi’s eukaryotic cell properties with human’s. Infection rate also increase in the past few years. Toxoplasma gondii infects one third of the human population and could cause dangerous effect for fetus and low immune system patients. However, available antitoxoplasmosis drugs could cause severe side effects. Therefore, new candidate for antifungal and antitoxoplasmosis drugs with mild or less side effects and safe are needed. Red bulbs of Eleutherine americana (Aubl.) Merr. ex K.Heyne has been known for its high content of naphtoquinones that have antifungal and antiparasitic acitivity. In silico interaction study was performed between 31 compounds from Eleutherine americana (Aubl.) Merr. ex K.Heyne with alternative protein targets for antifungal and antitoxoplasmosis activity with molecular docking method. In this research, N-Myristoyltransferase (PDB ID: 1IYL) and one of ORPs (oxysterol-binding-protein (OSBP)-related proteins), which is Osh4, (PDB ID: 1ZHX) were used as antifungal protein targets and enoyl-acyl carrier reductase (PDB ID: 2O2S) and calcium-dependent protein kinase-1 (PDB ID: 4M84) were used as antitoxoplasmosis protein targets. 3D structures were made with GaussView 6.0 Program then optimized with Gaussian 09W Program. Protein targets were prepared with Discovery Studio Program. Docking method was validated by re-docking native ligands with protein targets. Acceptance criteria of this validation is RMSD (root mean square deviation) value less than 2 Å. After that, the 31 compunds are docked to protein targets with AutoDock 4.2.6 Program. Aquatic toxicity prediction was performed to deterimine its safety lavel on aquatic organisms with ECOSAR V2.0 Program. This research results compounds that have smaller free binding energy than its positive control with low aquatic toxicity for antifungal protein targets Osh4 and CaNMT is ?-sitosterol with a free binding energy of -11,55 kcal/mol and -11,18 kcal/mol, and for antitoxsoplasmosis protein targets TgPNP and TgCDPK1 is ?-sitosterol with a free binding energy of -8,06 kcal/mol and -10,29 kcal/mol, respectively.